Maxillofacial infection. A retrospective evaluation of eight years - Bruno Veronez; Fernando Pando de Matos; Marcelo Silva Monnazzi; Alexander Tadeu Sverzut; Cássio Edvard Sverzut; Alexandre Elias Trivellato (Universidade Estadual de Campinas, 2015)
Aim: To evaluate medical records from patients who had maxillofacial infections between August 2002 and May 2010. Methods: Analysis of 157 patients' data looking for epidemiology, causes of the infection, type of treatment established and complications. Results: 113 patients had odontogenic infections and 44 had non-odontogenic infections. The white ethnicity was the most affected (64.33%), prevailing the men (53.5%). The odontogenic infections occurred mostly at the mandible (55.74%), involving the posterior teeth (82%). Dental decay was the main etiology (90.90%). The most affected facial anatomic region was the submandibular (42.85%). Surgical treatment was required in 76% of the cases. Conclusions: Maxillofacial infections should be treated as soon as possible. Even without culture and antibiogram results, it was possible to treat the infection and to reestablish tissue function.